Conformational analysis and intramolecular interactions in monosubstituted phenylboranes and phenylboronic acids - Silla, Josué M.; Cormanich, Rodrigo A.; Rittner, Roberto; Freitas, Matheus P. (Beilstein Journal of Organic Chemistry, 2013)
A 1TSJF,H(O) coupling pathway, dictated by a hydrogen bond, in some 2-fluorobenzoic acids has been observed, while such an interaction does not occur in 2-fluorophenol. Thus, this work reports the conformational analysis of 2-fluorophenylboronic acid (1), in order to evaluate a possible intramolecular OH∙∙∙F hydrogen bond in comparison to an nF→pB interaction, which mimics the quantum nF→σ*OH hydrogen bond that would be expected in 2-fluorophenol. 2-Fluorophenylborane (3), which does not experience hydrogen bonding, was used to verify whether nF→pB interaction governs the conformational equilibrium in 1 due to a predominant OH∙∙∙F hydrogen bond or to other effects. A series of 2-X-phenylboranes (X = Cl, Br, NH2, PH2, OH and SH) were further computationally analyzed to search for electron donors to boron, capable of influencing the conformational equilibrium. Overall, the intramolecular OH∙∙∙F hydrogen bond in 1 is quite stabilizing and dictates the 1hJF,H(O) coupling constant. Moreover, electron donation to the empty p orbital of boron (for noncoplanar BH2 moiety relative to the phenyl ring) is also significantly stabilizing for the NH2 and PH2 derivatives, but not enough to make the corresponding conformers appreciably populated, because of steric effects and the loss of πCC→pB resonance. Thus, the results found earlier for 2-fluorophenol about the lack of intramolecular hydrogen bonding are now corroborated.
Keywords: conformational analysis; hydrogen bond; interactions with boron; monosubstituted phenylboranes; phenylboronic acids